PENGARUH LABEL HALAL, VARIASI PRODUK, KUALITAS PRODUK DAN HARGA KOMPETITIF TERHADAP MINAT BELI - Sopingi, Imam; Haryanti, Peni; Santoso, Rohmad Prio (ITB AAS Indonesia Surakarta, 2024)
This study aims to analyze the effect of halal labels, product variety, product quality, and competitive prices on consumer buying interest. In the era of globalization where consumer preferences are increasingly diverse, these factors can be the main attraction for consumers in choosing products. The research method used is a survey through a questionnaire given to 527 respondents who are potential consumers. The collected data were analyzed using multiple linear regression. The results showed that the halal label has a significant positive effect on consumer buying interest. Consumers tend to choose products that have a halal label as a consideration of their halalness. In addition, product variety and product quality also have a significant positive influence on purchase intention. Consumers tend to be more interested in products with a variety of variations and have good quality. In addition, competitive prices also have a significant influence on consumer buying interest. These findings provide insight for producers and marketers to understand the importance of halal labeling, product variety, and product quality as well as competitive prices in increasing consumer buying interest. In addition, this study also provides a basis for further research on other factors that can influence consumer buying interest.